Analisis Vulnerability Assessment Sistem Informasi Pendidikan, Pelatihan PT Azure Samudera Karsa Menggunakan ZAP - Soni Ayi Purnama (PPPM Institut Teknologi Pagar Alam, 2025)
This study aims to analyze the security of the educational and training information system at PT Azure Samudera Karsa using the vulnerability assessment method. Enhancing the security of information systems is a key priority in order to improve the credibility and quality of the educational and training services provided by PT Azure Samudera Karsa. In today's digital era, information systems that are vulnerable to cyberattacks can lead to various negative consequences, including data breaches, information manipulation, and operational disruptions. Therefore, security evaluation becomes a crucial aspect that must not be overlooked. The tool used to assess the security of the educational and training information system at PT Azure Samudera Karsa is Zed Attack Proxy (ZAP), an open-source application commonly used to detect security vulnerabilities in web applications. The results of the vulnerability assessment revealed three levels of alerts: 3 alerts at the medium level, 6 alerts at the low level, and 3 informational alerts, totaling 13 alerts. These findings serve as an important basis for management to take immediate corrective actions to minimize risks and enhance the protection of the system in use.